Factors correlated with occupational stress among university lecturers - Gunawan, Elvine; P, Deo; T, Hidayat; V, Pandia; S, Iskandar; PS, Yuni; N, Sylviana; I, Akbar; R, Farenia; K, Wahyu; A, Purba; Hatta Sidi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Lecturers are expected to cope with stress in their workplace in order to continue to be productive. The demand to fulfill targets will increase the incidence of occupational stress. The aim of the study was to determine the factors associated with occupational stress among state university lecturers in Bandung, Indonesia. The study was carried out on 354 state university lecturers in Bandung, who came to the research location during May 2017. It was conducted by means of a diagnostic survey with the use of the Self Reporting Questionnaire (SRQ), Spiritual Wellness Inventory-R (SWI-R), Social Readjustment Rating Scale (SRRS), Miller Smith lifestyle assessment inventory, and Occupational Stress Scale (OSC). A total of 330 respondents became our study subjects with response rate of 92.94%. A correlation bivariate was applied to analyse the correlation of external and internal factors with occupational stress. The statistical analysis was conducted by means of SPSS Statistics 18.0 with p≤0.05. From 330 lecturers, there were 153 (46.4%) males and 177 (53.6%) females. The marital status included 257 (77.9%) married, 27 (8.2%) single, while 46 (13.9%) did not answer. The results proved the existence of a correlation between life, stress event, life style, mental emotional disorders, with occupational stress. The spirituality factors contributed to occupational stress were selfworth, control, and connectedness. Lecturer had to cope with occupational stress. There are some factors, which could influence occupational stress among lecturers.